Factors affecting basket catheter detection of real and phantom rotors in the atria: A computational study - Martinez-Mateu, Laura; Romero, Lucia; Ferrer-Albero, Ana; Sebastian, Rafael; Rodríguez Matas, José F.; Jalife, José; Berenfeld, Omer; Saiz, Javier (PLOS Computational Biology, 2018)
Author summary In computer simulations we determined the accuracy of using multiple-electrode basket catheters to detect atrial fibrillation sources (rotors) during an ablation procedure. We used a realistic 3D atrial model and a virtual multiple-electrode basket catheter placed in three different positions inside the right atrium. The ability to detect a true rotor depended on three major factors: 1) the position of the basket inside the atrium, 2) the distance between the electrodes and the atrial wall, and 3) the inter-electrode distance. When the electrodes were not in full contact with the atrial wall far-field sources predominated on the recorded signal. As a consequence, phantom rotors were generated on the maps. Interpolation of the signals increased the false rotor incidence, whereas increasing the electrode density decreased it. We conclude that the appearance of false rotors might contribute to AF ablation procedure failure because the physician may erroneously target atrial tissue locations where no true rotor exists.